Anatase TiO2 nanosheet : an ideal host structure for fast and efficient lithium insertion/extraction - Chen, Jun Song (2013)
Anatase TiO2 nanosheets with largely exposed (0 0 1) facets have been synthesized by a modified method. Exploitation of these nanosheets as a host structure for reversible lithium insertion/extraction has been investigated. It is found that these TiO2 nanosheets manifest much lower initial irreversible losses compared to other anatase TiO2 nanostructures, and excellent cycling performance at a charge–discharge rate as high as 20 C. The superior reversible lithium storage capability can be attributed to the ultrathin nanosheet structure: a large exposed effective area and a very short diffusion path. It thus attests the promising use of these anatase TiO2 nanosheets in high-power lithium–ion batteries.